The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/jmv.20106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of crimean‐congo hemorrhagic fever virus in Iran

Abstract: Crimean-Congo hemorrhagic fever (CCHF) is a potentially fatal disease caused by a tick-borne virus in the family Bunyavridae. The disease occurs in parts of Africa, Asia, Middle East, and Eastern Europe. During recent years, an increasing number of human CCHF cases have been diagnosed in Iran, but very little information is available on the prevalence and genetic diversity of CCHFV in Iran. In the present study, CCHF virus (CCHFV) isolates from nine Iranian patients infected during 2002 were examined genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 36 publications
3
73
0
Order By: Relevance
“…Cases in humans were first observed in 1999, and have since been reported in most provinces (Chinikar et al, 2004;Chinikar et al, 2010). In neighboring Iraq, surveillance was interrupted by civil unrest and war for nearly a decade, but a number of cases of CCHF have recently been reported (Majeed et al, 2012).…”
Section: The Middle Eastmentioning
confidence: 99%
“…Cases in humans were first observed in 1999, and have since been reported in most provinces (Chinikar et al, 2004;Chinikar et al, 2010). In neighboring Iraq, surveillance was interrupted by civil unrest and war for nearly a decade, but a number of cases of CCHF have recently been reported (Majeed et al, 2012).…”
Section: The Middle Eastmentioning
confidence: 99%
“…The partial sequences described in this study have been deposited in the GenBank database under Accession Nos. KT588640, KT588641 and KT588642 [8].…”
Section: Laboratory Testsmentioning
confidence: 99%
“…This method evaluates the topologies of different trees and chooses the best tree based on a specified model. This model is based on the evolutionary process that can account for the conversion of one sequence into another [8].…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Crimean-Congo Haemorrhagic Fever Virus (CCHFV) is a single-stranded RNA virus with three segments (large, medium, and small), two envelope proteins (Gn and Gc) and an RNA-dependent RNA polymerase [1][2][3]. Studies have found the GC protein to be the target-binding protein as well as an important mediator for virus entry [4]. Variations in small segments of RNA help to group the virus into seven different genotypes designated Africa-1, Africa-2, Africa-3, Europe-1, Europe-2, Asia-1 and Asia2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%